The Effect of Counseling Based on EX-PLISSIT Model on Sexual Dysfunction and Quality of Sexual Life of Married Women with Multiple Sclerosis: A Randomized Controlled Clinical Trial. - Azari-Barzandig, Roya; Sattarzadeh-Jahdi, Niloofar; Nourizadeh, Roghaiyeh; Malakouti, Jamileh; Mousavi, Saeed; Dokhtvasi, Gasem (Sexuality & Disability, 2020)
Sexual dysfunction is one of the most common complaints of patients with multiple sclerosis (MS). The study aimed to determine the effect of counseling based on the extended PLISSIT model (Permission, Limited Information, Specific Suggestion, and Intensive Therapy) on sexual dysfunction and the quality of sexual life of married women with MS. This randomized clinical trial was performed on 70 married women with MS aged between 18 and 45 years referring to the MS Association of Tabriz, Iran. The data were collected using a demographic questionnaire, Multiple Sclerosis Intimacy and Sexuality Questionnaire-19 (MSISQ-19), Sexual Quality of Life for a Female, Fatigue Severity Scale, and Beck Depression Inventory-Short Form Items (BDI-13). A neurologist rated the disability level using the Expanded Disability Status Scale. Using randomization, the participants with a score of 4 or 5 in each item of MSISQ-19 were assigned to counseling and the control group, with block sizes of four and six and allocation ratio of 1:1. The intervention group attended a counseling session or more if needed, based on the EX-PLISSIT model. Data were analyzed using SPSS software (Version 25). Independent t test and ANCOVA were used to analyze the data. After intervention, there was a significant difference between the two groups in terms of primary and tertiary sexual dysfunctions [AMD, − 7.84; 95% CI − 14.82 to − 0.86; P = 0.02]. Despite an increased mean score of quality of sexual life in the intervention group after counseling, there was no statistically significant difference between the two groups [AMD, 9.29; 95% CI − 1.46 to 20.04; P = 0.08]. Although counseling based on EX-PLISSIT had a positive effect on decreasing sexual dysfunction, it could not improve the quality of sexual life of women suffering from MS. Applying sexual counseling approaches with a focus on couple counseling is suggested for improving the quality of sexual life.